TET3-facilitated differentiation of human umbilical cord mesenchymal stem cells into oligodendrocyte precursor cells for spinal cord injury recovery - Yubo Zhang; Zhibin Peng; Man Guo; Yangyang Wang; Jingsong Liu; Yishu Liu; Mi Li; Tianli Wei; Pengfei Li; Yingwei Zhao; Yansong Wang (Journal of Translational Medicine)
Abstract Background Spinal cord injury (SCI) inflicts a severe burden on patients and lacks effective treatments. Owing to the poor regenerative capabilities of endogenous oligodendrocyte precursor cells (OPCs) following SCI, there is a growing interest in alternative sources, such as human umbilical cord mesenchymal stem cells (HUCMSCs). TET3 is a key DNA demethylase that plays an important role in neural differentiation, but its role in OPC formation is not well understood. This study aimed to explore the TET3-mediated one-step induction of HUCMSCs into OPCs. Methods In vitro, HUCMSCs were induced into OPCs following TET3 overexpression. Changes of methylation and hydroxymethylation during differentiation were monitored, mechanisms involved in the TET3-driven HUCMSC differentiation into OPCs were identified by RNA sequencing. Methylation levels in NG2 and PDGFRA promoter region were detected using Bisulfite Polymerase Chain Reaction (BSP).In vivo, therapeutic effects of iOPCs were evaluated through a rat Allen’s SCI model. Results The in vitro analysis confirmed that TET3 enhances HUCMSC differentiation into OPCs, validitied by specific marker expression. The induced OPCs (iOPCs) exhibited methylation and hydroxymethylation patterns similar to native OPCs. BSP analysis demonstrated that TET3 overexpression significantly reduced CpG island methylation in the NG2 and PDGFRA promoter regions. RNA sequencing revealed that TET3 induces iOPCs to express a series of genes essential for OPC formation while inhibiting the signaling pathways that hinder OPC development. In a rat model of SCI, TET3-overexpressing HUCMSCs appear to have the potential to differentiate into iOPCs in vivo, suppressed secondary injury, and promoted functional recovery. The therapeutic effects of iOPCs on SCI were superior to those of standard mesenchymal stem cell treatments. Conclusions Our study demonstrated that TET3-mediated demethylation reshapes the methylation patterns of HUCMSCs, enabling their efficient one-step conversion into OPCs and significantly reducing the time required for cell preparation. This approach offers a potential strategy for early intervention in SCI. In an SCI model, TET3-induced OPCs contributed to spinal cord repair, providing novel insights into cell therapy strategies for SCI through the lens of methylation regulation.